III–V semiconductor resonators: A new strategy for broadband light perfect absorbers. (3rd October 2017) - Liu, Xiaoshan; Chen, Jian; Liu, Jiasong; Huang, Zhenping; Yu, Meidong; Pan, Pingping; Liu, Zhengqi
Abstract: Broadband light perfect absorbers (BPAs) are desirable for applications in numerous optoelectronics devices. In this work, a semiconductor-based broadband light perfect absorber (S-BPA) has been numerically demonstrated by utilizing plasmonlike resonances of high-index semiconductor resonators. A maximal absorption of 99.7% is observed in the near-infrared region. By taking the absorption above 80% into account, the spectral bandwidth reaches 340 nm. The absorption properties mainly originate from the optical cavity modes induced by the cylinder resonators and ultrathin semiconductor film. These optical properties and simple structural features can maintain the absorber platform with wide applications in semiconductor optoelectronics.